Resilience building in Ethiopia: Analysis of key informant interviews - Domènech, Laia; Tesfatsion, Semhar; Ringler, Claudia; Theis, Sophie (International Food Policy Research Institute, 2019)
A key element of the climate resilience Gender, Climate Change, and Nutrition Integration Initiative (GCAN) framework is understanding Ethiopia’s response options and the decision-making context. To reduce dependency on emergency aid and the vulnerability of communities and ecosystems to climatic shocks, a series of programs and projects were initiated by the Ethiopian government, multilateral agencies, and bilateral donors. These aimed to build resilience and simultaneously boost economic growth, create jobs and livelihoods, and strengthen access to health and education for all communities.